Penerapan Strategi Pembelajaran Inkuiri Dalam Meningkatkan Kemampuan Berpikir Kritis Pada Pembelajaran Pendidikan Agama Islam - Lathiva Wulandari; Cindy Aulia Safmi; Gusmaneli . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Learning strategies are one of the important factors in improving the quality of the learning process, especially in Islamic Religious Education (PAI). One of the strategies that can be applied is the inquiry-based learning strategy, which emphasizes the active involvement of students in discovering knowledge independently. This study aims to examine the concepts, procedures, advantages, disadvantages, and implementation of inquiry-based learning strategies in PAI learning. The method used in this study is a literature review with a qualitative approach, drawing on relevant books and scientific journal articles. The results of the study indicate that inquiry-based learning strategies are capable of improving students’ critical thinking skills, activeness, and understanding. In addition, the implementation of this strategy will be more optimal when combined with learning media such as mind mapping. However, this strategy also has some limitations, such as requiring relatively more time and teacher readiness in designing systematic learning activities. Therefore, inquiry-based learning strategies can serve as an effective alternative in improving the quality of PAI learning.